Legal regulation of copyright in Ukraine: borrowing from the experience of European countries - Dilihyl, Alina (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
The article is devoted to the analysis of the legal regulation of copyright in Ukraine and the possibilities of borrowing the experience of European countries in this field. The main aspects of copyright in Ukraine are considered, in particular, the author's right to remuneration for the use of his work, the right to reproduction, distribution, and others. A comparative analysis with the experience of European countries regarding the protection of copyright was carried out. The possibility of introducing the best practices of European countries into the legislation of Ukraine with the aim of increasing the effectiveness of copyright protection and stimulating the creativity of creators is highlighted. The article also examines the main problems existing in the field of copyright in Ukraine, such as insufficient effectiveness of legal protection, shortcomings in legislation and executive practice. It is noted that some European countries have a more developed copyright protection system, which can be a model for Ukraine in improving its legislation.The possibility of harmonizing Ukrainian legislation with European standards in the field of copyright, in particular by harmonizing legislation with international conventions and directives of the European Union, was also explored. The author concludes that there is a need for active interaction and exchange of experience between Ukraine and European countries in the field of legal regulation of copyright in order to achieve high standards of copyright protection and to stimulate the development of the cultural and creative industry.Adopting the experience of European countries may be a useful direction for further development of Ukrainian copyright regulation. This could include harmonisation of legislation, strengthening of legal protection, improvement of enforcement practices, development of infrastructure for rights protection, and stimulation of innovation and creativity. In general, the implementation of best practices from European countries can help to improve the effectiveness of copyright protection and stimulate creativity in Ukraine.